Acute purpura fulminans—a rare cause of skin necrosis: A single‐institution clinicopathological experience. (13th September 2020) - Brozyna, Jeremy R.; Sardiña, Luis A.; Sharma, Anurag; Theil, Karl S.; Bergfeld, Wilma F.
Abstract: Background: Purpura fulminans, an uncommon syndrome of intravascular thrombosis with hemorrhagic infarction of the skin, is often accompanied by disseminated intravascular coagulation (DIC) and multi‐organ failure, and may ultimately lead to death. Methods: Herein, we document 13 skin biopsies from 11 adult patients with the clinical diagnosis of sepsis and confirmed histopathologic diagnosis of intravascular thrombosis and/or DIC, compatible with acute infectious purpura fulminans (AIPF). Detailed history and clinical examination were performed, and the lesions were correlated with histopathologic findings. Any underlying medical disease was taken into consideration. Results: There were 5 males and 6 females with lower extremity or peri‐incisional purpuric skin lesions. The most important comorbidities identified were a history of surgical procedure or neoplasm, although 4 patients had no relevant underlying history. Most skin biopsies revealed focal epidermal ischemia or necrosis and 3 showed full‐thickness epidermal necrosis. In the underlying dermis, there were fibrin thrombi in superficial and deep blood vessels with acute inflammation. Changes of an inflammatory destructive vasculitis were identified in 5 cases. No bacteria or fungi were identified on histopathology. Conclusions: AIPF is a rapidly‐progressing medical emergency which may be identified by histopathology in culture‐negative cases. Biopsies may show neutrophilic infiltrate without infective organisms.